Environmental modeling for sustainable regional development : system approaches and advanced methods - Olej, Vladimir, 1954-; Obrsalova, Ilona, 1945-; Krupka, Jiri, 1962- (Hershey, PA : Information Science Reference, 2011)
"This book presents methods and case studies for researchers and policy makers searching for alternative solutions for problems in regional sustainable development, taking into account socio-economic and environmental dimensions in a system integrated approach"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Sustainable development -- Econometric models; Rural development -- Environmental aspects; Regional planning -- Environmental aspects